Dispersal, isolation and diversification with continued gene flow in an Andean tropical dry forest. Issue 13 (20th June 2017) - Toby Pennington, R.; Lavin, Matt
Abstract : The Andes are the world's longest mountain chain, and the tropical Andes are the world's richest biodiversity hot spot. The origin of the tropical Andean cordillera is relatively recent because the elevation of the mountains was relatively low (400–2500 m palaeoelevations) only 10 MYA with final uplift being rapid. These final phases of the Andean orogeny are thought to have had a fundamental role in shaping processes of biotic diversification and biogeography, with these effects reaching far from the mountains themselves by changing the course of rivers and deposition of mineral‐rich Andean sediments across the massive Amazon basin. In a recent issue of Molecular Ecology, Oswald, Overcast, Mauck, Andersen, and Smith (2017) investigate the biogeography and diversification of bird species in the Andes of Peru and Ecuador. Their study is novel in its focus on tropical dry forests (Figure 1) rather than more mesic biomes such as rain forests, cloud forests and paramos, which tend to be the focus of science and conservation in the Andean hot spot. It is also able to draw powerful conclusions via the first deployment of genomic approaches to a biogeographic question in the threatened dry forests of the New World. Abstract : see also the Perspective by Oswald et al